2022
DOI: 10.3390/medicina58121757
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiological Features of Interstitial Lung Diseases Associated with Polymyositis and Dermatomyositis

Abstract: Polymyositis and dermatomyositis are autoimmune idiopathic systemic inflammatory diseases, characterized by various degrees of muscle inflammation and typical cutaneous lesions—the latter found in dermatomyositis. The underlying pathogenesis is characterized by a high level of uncertainty, and recent studies suggest diseases may have different immunopathological mechanisms. In polymyositis, components of the cellular immune system are involved, whereas in dermatomyositis, the pathogenesis is mainly mediated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 86 publications
1
7
0
Order By: Relevance
“…7 Previous studies have suggested that different ILD patterns in patients with IIM are associated with different prognoses. 8 However, large-scale clinical studies exploring the exact radiological and pathological features of anti-MDA5+DM-associated ILD (anti-MDA5+DM ILD) are still lacking, with only a few case reports and small-sample studies. [9][10][11] Accordingly, we aimed to clarify the clinical characteristics, radiological features and pathological features of anti-MDA5+DM ILD in a relatively large cohort and to identify the disease progression profile of different patterns of ILD.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%
“…7 Previous studies have suggested that different ILD patterns in patients with IIM are associated with different prognoses. 8 However, large-scale clinical studies exploring the exact radiological and pathological features of anti-MDA5+DM-associated ILD (anti-MDA5+DM ILD) are still lacking, with only a few case reports and small-sample studies. [9][10][11] Accordingly, we aimed to clarify the clinical characteristics, radiological features and pathological features of anti-MDA5+DM ILD in a relatively large cohort and to identify the disease progression profile of different patterns of ILD.…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 99%
“…PM and DM are autoimmune systemic inflammatory diseases characterized by proximal muscle weakness, systemic involvement and cutaneous manifestations, the latter a characteristic of DM. 72 The incidence of DM and PM is rare, ranging from 1.2 to 66 new cases per 1,000,000 person-years, and like other CTDs demonstrates a female predilection. 73 The presence of ILD is more strongly associated with having a positive anti-Jo 1 antibody with a prevalence of approximately 50 to 70%.…”
Section: Dermatomyositis/polymyositismentioning
confidence: 99%
“…OP pattern is also described in PM/DM, characterized by patchy ground-glass opacities and in some cases demonstrating a characteristic nodular reverse halo appearance (central area of ground-glass opacification surrounded by peripheral rim of consolidation). 72 Anti-synthetase syndrome is a clinicoserologic syndrome associated with DM/ PM, defined by the association of an autoantibody against an aminoacyl-transfer RNA synthetase and various clinical manifestations. Debray et al described CT findings in 33 patients with anti-synthetase syndrome who had signs of ILD on CT and showed predominantly NSIP and NSIP-OP CT pattern.…”
Section: Dermatomyositis/polymyositismentioning
confidence: 99%
“…Idiopathic inflammatory myopathy is a rare disorder that occurs in approximately 14-17 per 100,000 people. [9] Pulmonary involvement occurs in 9-60% of idiopathic inflammatory myopathy; it causes about 40% of disease-related mortality. [6,9] Diagnosis may be delayed in patients whose initial sign is diffuse interstitial lung disease and who are receiving corticosteroid therapy due to the suppression of musculoskeletal findings.…”
Section: Idiopathic Inflammatory Myositis First Described By Bohan Andmentioning
confidence: 99%
“…[9] Pulmonary involvement occurs in 9-60% of idiopathic inflammatory myopathy; it causes about 40% of disease-related mortality. [6,9] Diagnosis may be delayed in patients whose initial sign is diffuse interstitial lung disease and who are receiving corticosteroid therapy due to the suppression of musculoskeletal findings. [10] In our case, the initiation of steroid therapy with the primary diagnosis of COVID-19 infection caused a temporary improvement in symptoms.…”
Section: Idiopathic Inflammatory Myositis First Described By Bohan Andmentioning
confidence: 99%